A new continuity with colonial administration: participation in development management - Cooke, Bill (Third world quarterly, 2003)
Development management owes an unacknowledged debt to colonial administration, specifically to indirect rule. Development management, as opposed to development administration, has newly adopted a specific set of managerialist participatory methods, to achieve 'ownership' of development interventions. These methods are particularly evident in World Bank/IMF implementation of Poverty Reduction Strategy Papers (PRSPs) and Comprehensive Development Frameworks (CDFs). They have their conceptual foundation in action research, invented, it can justly be argued, by John Collier, Commissioner of the US Bureau of Indian (ie Native American) Affairs 1933-1945. Collier was a self-proclaimed colonial administrator, and remained an advocate of indirect rule as late as 1963. Evidence is presented to show his development of action research was a tool of indirect rule. Achieving 'empowerment' through participation was at its very beginning, therefore, subject to the colonialist's asserted sovereign power; and the limited autonomy it granted was a means of maintaining that power. (Original abstract)